[Portuguese original] Sources of knowledge of teacher-coaches of school volleyball in Catarina - Marcelino, Anderson (2024)
The study aimed to identify the sources of knowledge most valued by the teachers-coaches of school volleyball in Santa Catarina, considering academic training, federative training, experience as an athlete, and professional development cycles. The study included 52 school volleyball coaches who worked in the state stages of the Santa Catarina School Games in 2022. Data were collected through the Coach Training Profile test, which includes the dimensions of academic education, the experience of the athlete, and professional experience. Data were analyzed using the software SPSS, version 20.0, with a significance level of p≤0.05. The results point to a greater appreciation of sources of knowledge from professional experience (42.08±5.79) and academic training (41.19±6.00) in the preparation of the training process. Licensed and/or licensed teacher-coaches, with less professional experience and without federative training, significantly value the sources of knowledge acquired during competitive sporting experiences as athletes.